Identidade do indígena no Paraná e desenvolvimento sustentável : conflitos entre diversidade cultural e inclusão social na contemporaneidade - Marconi, Thaís Almeida (2011)
The principle of sustainable development comprises the ability to attend to current needs without jeopardizing natural resources for future generations. This is the reason why sustainable development integrates contemporary emergent policies. The target of sustainable development is the population and is subject to governableness. Due to the dynamics of its activities and articulations maintained under the aegis of cultural diversity, human relationships are mobilized in the context of the planet Earth, whereas the places occupied politically and socially by different subjects are determined. Since cultural diversity is an aggregating factor of differences within existence conditions, the possibility of it becoming a sustainable development catalysis is established. This is due to the fact that sustainability implies in cultural homogeneity and the acculturation of a equality-promoting society. The conflict between these two political forces trigger the following question: When the didactic and paradidactic materials, employed in indigenous schools in the state of Paraná, Brazil, analyze history and the culture of native people and the ecosystem, do they constitute identities for the indigenous subject under the perspective of cultural diversity while taking into consideration the social and cultural mobilizations established by the national current inclusion policies? The complexity factor inherent to the issue on indigenous identity is the main focus of current research. It is actually based on the theories of French Discourse Analysis, on Cultural Studies and on History and comprise the following categories: discourse, enunciation function, history, memory, knowledge-power, governableness, biopower and identity for the analytic practice and developed by the archeo-genealogical descriptive and interpretative movement. Expecting that current investigation may contribute towards Text and Discourse Studies, especially those involved in indigenous causes, research establishes the modes by which indigenous identities are constructed through the principles of sustainable development policies in iconographic discourses circumscribed within the educational area. Results obtained from the established course taken and the analyses developed from the research corpus indicate that indigenous identity constitution is split and displaced to occupy discursively different sites. Consequently, it is not made up of a single whole. From the sustainable development's point of view, the indigenous identity constitution reveals itself to be an environment management without elderly people as the seat of knowledge and with children and young people as their substitutes. The displacement of the legitimate subject occurs through an inversion of roles. On the other hand, the indigene is the manager of the ecosystem and segregated to his territory, or rather, a re-signified mythic Indian. His condition as an included subject is guaranteed by political activity and by the universal participation in the common good or the ecosystem.